2014
DOI: 10.1136/bcr-2014-204706
|View full text |Cite
|
Sign up to set email alerts
|

Methaemoglobinaemia in a G6PD-deficient child treated with rasburicase

Abstract: A 5-year-old boy from the Congo, was admitted for hyperleucocytic acute lymphoblastic leukaemia, with a high risk of tumour lysis syndrome (TLS). He had splenomegaly and mediastinal lymphadenopathy on chest X-ray. We started steroids and hyperhydration with rasburicase to prevent TLS. Respiratory failure with mediastinal enlargement developed rapidly. A few hours after intensive care unit (ICU) admission, he was started on mechanical ventilation. Chemotherapy was started immediately given the strong suspicion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…Among the included studies, 21 studies reported 1 patient each, and 3 studies reported 2 patients each who developed methemoglobinemia followed by rasburicase administration. The majority of patients were previously diagnosed with lymphoma, T-cell or acute lymphoblastic leukaemia, Non-Hodgkin lymphoma, chronic lymphocytic leukaemia, Burkitt's lymphoma, and few were diagnosed with gout, Neuroendocrine tumour, Status epileptics, IgA variant or refractory aggressive multiple myeloma, sporadic adenomatous polyposis syndrome and metastatic colon cancer, pulmonary sarcoidosis and mycosis fungoides and AIDS 5,1032 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Among the included studies, 21 studies reported 1 patient each, and 3 studies reported 2 patients each who developed methemoglobinemia followed by rasburicase administration. The majority of patients were previously diagnosed with lymphoma, T-cell or acute lymphoblastic leukaemia, Non-Hodgkin lymphoma, chronic lymphocytic leukaemia, Burkitt's lymphoma, and few were diagnosed with gout, Neuroendocrine tumour, Status epileptics, IgA variant or refractory aggressive multiple myeloma, sporadic adenomatous polyposis syndrome and metastatic colon cancer, pulmonary sarcoidosis and mycosis fungoides and AIDS 5,1032 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…As rasburicase breaks down uric acid to allantoin, it also produces hydrogen peroxide, an oxidizing agent, as a byproduct. ( 1 , 46 , 47 ) Rasburicase-induced methemoglobinemia is a potentially serious adverse effect that has been documented in several patients with G6PD deficiency, ( 48 , 49 ) and rasburicase is thus contraindicated in patients with G6PD deficiency. A few patients in our cohort received rasburicase and were later determined to be G6PD deficient.…”
Section: Discussionmentioning
confidence: 99%
“…Of the reported cases of rasburicase-induced methemoglobinemia, 11 of the 15 patients tested for G6PD were found deficient (73%) [8][9][10][11][12][13][14]; however, this may be an underestimate, as some patients were only tested for the condition in the acute phase of illness. G6PD deficiency is a relative contraindication for methylene blue therapy; like rasburicase, it may exacerbate methemoglobinemia and cause hemolysis [15].…”
Section: To the Editormentioning
confidence: 99%